A dual-chain assembly pathway generates the high structural diversity of cell-wall polysaccharides in Lactococcus lactis - Theodorou, Ilias (J Biol Chem, 2019)
In Lactococcus lactis, cell-wall polysaccharides (CWPSs) act as receptors for many bacteriophages, and their structural diversity among strains explains, at least partially, the narrow host range of these viral predators. Previous studies have reported that lactococcal CWPS consists of two distinct components, a variable chain exposed at the bacterial surface, named polysaccharide pellicle (PSP), and a more conserved rhamnan chain anchored to, and embedded inside, peptidoglycan. These two chains appear to be covalently linked to form a large heteropolysaccharide. The molecular machinery for biosynthesis of both components is encoded by a large gene cluster, named cwps. In this study, using a CRISPR/Cas-based method, we performed a mutational analysis of the cwps genes. MALDI-TOF MS-based structural analysis of the mutant CWPS combined with sequence homology, transmission EM, and phage sensitivity analyses enabled us to infer a role for each protein encoded by the cwps cluster. We propose a comprehensive CWPS biosynthesis scheme in which the rhamnan and PSP chains are independently synthesized from two distinct lipid-sugar precursors and are joined at the extracellular side of the cytoplasmic membrane by a mechanism involving a membrane-embedded glycosyltransferase with a GT-C fold. The proposed scheme encompasses a system that allows extracytoplasmic modification of rhamnan by complex substituting oligo-/polysaccharides. It accounts for the extensive diversity of CWPS structures observed among lactococci and may also have relevance to the biosynthesis of complex rhamnose-containing CWPSs in other Gram-positive bacteria.